Long-term production of BDNF and NT-3 induced by A91-immunization after spinal cord injury - Martiñón, Susana (BMC Neurosci, 2016)
BACKGROUND: After spinal cord (SC)-injury, a non-modulated immune response contributes to the damage of neural tissue. Protective autoimmunity (PA) is a T cell mediated, neuroprotective response induced after SC-injury. Immunization with neural-derived peptides (INDP), such as A91, has shown to promote—in vitro—the production of neurotrophic factors. However, the production of these molecules has not been studied at the site of injury. RESULTS: In order to evaluate these issues, we performed four experiments in adult female Sprague–Dawley rats. In the first one, brain derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) concentrations were evaluated at the site of lesion 21 days after SC-injury. BDNF and NT-3 were significantly increased in INDP-treated animals. In the second experiment, proliferation of anti-A91 T cells was assessed at chronic stages of injury. In this case, we found a significant proliferation of these cells in animals subjected to SC-injury + INDP. In the third experiment, we explored the amount of BDNF and NT3 at the site of injury in the chronic phase of rats subjected to either SC-contusion (SCC; moderate or severe) or SC-transection (SCT; complete or incomplete). The animals were treated with INDP immediately after injury. Rats subjected to moderate contusion or incomplete SCT showed significantly higher levels of BDNF and NT-3 as compared to PBS-immunized ones. In rats with severe SCC and complete SCT, BDNF and NT-3 concentrations were barely detected. Finally, in the fourth experiment we assessed motor function recovery in INDP-treated rats with moderate SC-injury. Rats immunized with A91 showed a significantly higher motor recovery from the first week and up to 4 months after SC-injury. CONCLUSIONS: The results of this study suggest that PA boosted by immunization with A91 after moderate SC-injury can exert its benefits even at chronic stages, as shown by long-term production of BDNF and NT-3 and a substantial improvement in motor recovery.